EFEK PROMOSI ASI EKSKLUSIF PADA PERTUMBUHAN ANAK - Kun Aristiati Susiloretni; Yayi Suryo Prabandari; Hamam Hadi; Yati S Sunarto (GIZI INDONESIA, 2013)
ABSTRACT EFFECT OF PROMOTION OF EXCLUSIVE BREASTFEEDING IN CHILD GROWTH The effectiveness of exclusive breastfeeding promotion on increasing its duration and proportion has been revealed, but not on child growth. The objective of this article is to assess the effect of multilevel promotion of exclusive breastfeeding on child growth. A quasi experiment of the promotion with pre-post-test control group design was applied at Demak, Central Java Province. A total of 163 pregnant women and their families were participated. Children’ growths were measured at 2, 4, 6, and 28 months. The results showed that weight for age z score overtime, weight gained at 2 to 6 months and weight for age z score of 6-28 months were improved. There was no significance different of slope overtime on (a) length and weight gain, (b) length-for-age, and weight-for-length z scores, and (c) under nutrition prevalence between the intervention and the control group. The multilevel promotion of exclusive breastfeeding could improve weight for age z score but was not found to growth faltering. It is suggested to do the same study but using gold standard randomized controlled trial considered confounding factors. In addition, the local government could adopt the method and material used in this study. Keywords: multilevel promotion, growth increment, z score